Antibacterial, conductive, and osteocompatible polyorganophosphazene microscaffolds for the repair of infectious calvarial defect. Issue 12 (26th June 2021) - Huang, Yiqian; Du, Zhiyun; Zheng, Tianyi; Jing, Wei; Liu, Huanhuan; Liu, Xue; Mao, Jianping; Zhang, Xu; Cai, Qing; Chen, Dafu; Yang, Xiaoping
Abstract: Many osteoconductive and osteoinductive scaffolds have been developed for promoting bone regeneration; however, failures would occur in osteogenesis when the defect area is significantly infected while the biomaterials have no antibacterial performances. Herein, a kind of multipurpose PATGP@PDA + Ag microspheres was prepared via emulsion method by using a conductive aniline tetramer (AT) substituted polyphosphazene (PATGP), followed by polydopamine (PDA) modification and silver nanoparticles (AgNPs) loading. The PATGP@PDA + Ag microspheres demonstrated a strong antibacterial activity against Staphylococcus aureus both in vitro and in vivo, while showing no cytotoxicity at an optimized AgNPs loading amount. Due to the electron‐donor structure of the AT moieties, the PATGP@PDA + Ag microspheres displayed antioxidant capacities to scavenge reactive oxygen species (ROS). Due to their phosphorus‐rich feature, the PATGP@PDA + Ag microspheres favored the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs). As controls, nonconductive microspheres (PAGP@PDA, PAGP@PDA + Ag) were prepared similarly by using poly[(ethylalanine)(ethylglycyl)]phosphazene (PAGP). By co‐implanting these microspheres with S. aureus into rat calvarial defects, among them, it was determined that the PATGP@PDA + Ag microspheres achieved the most abundant neo‐bone formation, benefiting from their antibacterial, antioxidant and osteogenic activities. These results revealed that AgNPs loaded scaffolds made of conductive polyphosphazenes were promising for the regeneration of infected bone defects. Abstract :